The hepatoprotective effect of Arnebia euchroma hydro-alcoholic extract against liver toxicity induced by CCl4 in mice - Mohammad Shokrzadeh; Mohammad Azadbakht; Hamidreza Shakibamanesh (Mazandaran University of Medical Sciences, 2017)
Arnebia euchroma is from Boraginaceae family. Various therapeutic effects have been reported for different species of this plant. The aim of this study was to investigate antioxidant activity of hydroalcoholic extract of the root of A. euchroma and its protective effect on hepatotoxicity induced by CCl4 in mice. In this experimental study, A. euchroma was extracted with ethanol solvent by maceration method. Antioxidant activity of the plant has been evaluated by the DPPH free radical scavenging method. Then, the hepatoprotective effect of A. euchroma was evaluated through determination the content of glutathione in liver tissue, ALP, AST, ALT serum levels and histopathology of liver in different groups. The total phenolic content determined as 0.56% per 100 g of plant was equivalent to gallic acid. The total flavonoid content was 0.079% per 100 g of plant that was equivalent to quercetin. The IC50 of the extract for free radical scavenging was obtained 139.2 µg/ml. The extract increased liver glutathione and serums ALP, AST, ALT that were decreased by CCl4 administration in animal. All protective effects were dose-dependent and the results of liver histopathology showed a significant improvement of inflammation and necrosis that were caused by CCl4 in mice. The results of this study revealed that the hydroalcoholic extract of A. euchroma root has an antioxidant effect and excellent hepatoprotection in mice.